Comparative Analysis of Early Outcomes In Polytetrafluoroethylene (Ptfe) Patch Versus Bovine Pericardial Patch for Monocusp For Right Ventricular Outflow Tract Reconstruction of Tetralogy of Fallot (Tof) Repair - Majid, Muhammad; Kamal Mehsood, Dawood; ul Haq, Intisar; Ali Khan, Nasir; Abdullah, Muhammad; Akram, Muhammad Adnan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare early outcomes of polytetrafluoroethylene patch (PTFE) versus bovine pericardial patch for monocusp in right ventricular outflow tract reconstruction of Tetralogy of Fallot (TOF) repair. Study design: Quasi-experimental study. Place and Duration of Study: Department of Paediatric and Congenital Cardiac Surgery, Armed Forces Institute of Cardiology and National Institute of Heart Diseases (AFIC-NIHD), Rawalpindi, Pakistan, from Jun 2024 to May 2025. Methodology: A total of 32 children aged ≤15 years, with transannular TOF were recruited through non-probability consecutive sampling and non-randomly allocated into groups based on the TOF repair technique: Group PTFE or Group bovine pericardial patch. All operative procedures were performed with median sternotomy under cardiopulmonary bypass (CPB) with moderate hypothermia. Early outcomes were compared between groups including peri-operative pulmonary regurgitation and residual right ventricular outflow tract pressure gradient (RVOT-PG), CPB time, aortic cross-clamp (ACC) time, ventilation time, Intensive Care Unit (ICU) stay and mortality. Results: Out of 32 patients, 19(58.80%) were male and 13(41.20%) were female while median age was 2.25 (6.50-1.58) years. Moderate pulmonary regurgitation (PR) was observed in 11.80% of the cases in PTFE group as compared to 29.40% of cases in Bovine group, however, this difference was not statistically significant (p>0.05) where RVOT-PG was significantly higher in the PTFE group (32.94±8.47 vs. 24.12±11.72 mmHg, p=0.01) on peri-operative echocardiogram. Conclusion: Similar early results were seen with RVOT reconstruction using PTFE and bovine pericardial monocusps, although it was statistically not significant, PTFE provided better protection against moderate pulmonary regurgitation.